Penerapan Model Pembelajaran MURDER Berbantuan Gamifikasi untuk Meningkatkan Kemampuan Pemahaman Konsep Matematika Siswa Kelas VIII di SMP Negeri 35 Medan - Tantri Sihite; Pardomuan N.J.M Sinambela (Journal on Education, 2023)
This study aims to improve the ability to understand mathematical concepts of VIII grade students at SMP Negeri 35 Medan by applying the MURDER learning model assisted by gamification. The subjects in this study were VIII grade students at SMP Negeri 35 Medan which amounted to 30 people. The type of research used was classroom action research, which was carried out in 2 cycles. Each cycle consists of 4 stages, namely planning, implementation, observation/evaluation and reflection. The results showed that students' mathematical concept understanding ability could improve after the MURDER learning model assisted by gamification was applied. The improvement was observed through the students' average score, which increased from 40.56 in the low category during cycle I to 68.47 in the medium category, and further increased during cycle II to 81.81 in the high category. The improvement was also evident in the students' classical ability, with 16 students (53.33%) achieving completion during cycle I, and 25 students (83.33%) achieving completion during cycle II. So it is concluded that the application of the MURDER learning model assisted by gamification can improve the ability to understand mathematical concepts of class VIII students at SMP Negeri 35 Medan.